Caprolactam from Renewable Resources: Catalytic Conversion of 5-Hydroxymethylfurfural into Caprolactone - Buntara, Teddy; Noel, Sebastien; Phua, Pim Huat; Melián-Cabrera, Ignacio; de Vries, Johannes G.; Heeres, Hero J. (Angewandte Chemie International Edition, 2011)
Renewable nylon: 5‐Hydroxymethylfurfural (HMF), which can be obtained from renewable resources such as D‐fructose, was converted into caprolactone with very good overall selectivity in only three steps. The new route involves two hydrogenation steps to obtain 1,6‐hexanediol, which was oxidatively cyclized to caprolactone, and then converted into caprolactam.